Extraction and identification of bioactive compounds from L. pumila - Afiqah, Yeop; Jessinta, Sandanasamy; Pang, Sook Fun; Sureena, Abdullah; Mashitah, Mohd Yusoff; Jolius, Gimbun (RMP Publications, 2019)
This paper presents the comparison of extraction methods between maceration extraction (ME) and ultrasonic assisted extarction (UAE) to the bioactive compounds yield (gallic acid, protocatechuic acid, epigallocatechin and rutin) of Labisia pumila. A grinded dried plant material with size ranging 246.58μm to 257.72μm was performed throughout this work. The gallic acid, protoctechuic acid, epigallocatechin and rutin qualification and quantification were performed using an ultra-performance liquid chromatography coupled photodiode array (UPLC-PDA). Exact match between the residence time from the plant extract and external standard was found indicating a presence of these four targeted bioactive compounds. It was found that UAE method has the highest extraction yield; gallic acid (0.0293 mg GA/g DW), protocatechuic acid (0.0081 mg PCA/g DW), epigallocatechin (0.0057 mg EGC/g DW) and rutin (0.0038 mg Rutin/g DW) compared to ME. The findings in this work may serve as a useful guide to obtain a highest extraction yield of these four targeted bioactive compounds from L. pumila.